2021
DOI: 10.1029/2020wr029473
|View full text |Cite
|
Sign up to set email alerts
|

Net Ecosystem Production of Lakes Estimated From Hypolimnetic Organic Carbon Sinks

Abstract: Primary production in the photic surface layer is at the onset of life and the trophic cascade in natural waters. The assimilation of carbon (C), phosphorus (P), nitrogen (N) and other nutrients as well as the release of oxygen (O 2 ) in the productive surface zone is reversed in the hypolimnion as organic particles settle through the water column to the sediment surface (Wetzel, 2001). If this cycling is excessive, the wellknown adverse effects of deep-water anoxia, accumulation of large amounts of deposited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…By applying the mass balance budgeting approach to deep oxygen profiles collected with the CTD probe, we found that the seasonal ecosystem respiration between 30 and 100 m depth was 23.2 mmol m −2 day −1 , or 37 g C m −2 (Figure ). The total ecosystem respiration (13.6 + 23.2 = 36.8 mmol m −2 day −1 ) is in very good agreement with the mean summer areal hypolimnetic remineralization derived from depletion rates in the historical time series (Schwefel et al., 2018; Steinsberger et al., 2020, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…By applying the mass balance budgeting approach to deep oxygen profiles collected with the CTD probe, we found that the seasonal ecosystem respiration between 30 and 100 m depth was 23.2 mmol m −2 day −1 , or 37 g C m −2 (Figure ). The total ecosystem respiration (13.6 + 23.2 = 36.8 mmol m −2 day −1 ) is in very good agreement with the mean summer areal hypolimnetic remineralization derived from depletion rates in the historical time series (Schwefel et al., 2018; Steinsberger et al., 2020, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…(Table 3). These values are comparable to the observed P:N ratio of seston in Lake Geneva (Steinsberger et al 2021).…”
supporting
confidence: 88%
“…The annual phosphorus uptake in the productive layer (P-uptake) to sustain PP is calculated from the annual P-budget, given by the difference of the source and sink terms of P load (Krishna et al 2021;Steinsberger et al 2021). The source terms include the watershed contributions of the bioavailable dissolved reactive phosphorus (from the rivers and wastewater treatment plants around Lake Geneva), represented as DRP 𝑖𝑛 , and the net difference of P stock in the epilimnion before and after the production period (Fig.…”
Section: Annual Phosphorus Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all autochthonous carbon settles to the sediment where it is available for methanogenesis. The ratio of autochthonous carbon that does settle is referred to as the "export ratio" and mean export rates across a range of studies are approximately 40 ± 20% (Baines & Pace, 1994;Berman et al, 2010;Darchambeau et al, 2005.;De Vicente et al, 2008;Ostrovsky & Yacobi, 2010;Steinsberger et al, 2021;Teodoru et al, 2013). Based on these studies, we use a constant export ratio of 40% across reservoirs.…”
Section: Autochthonous Inputmentioning
confidence: 99%